“Adaptabilidad de lineas promisorias y variedades de arroz ( oryza sativa L.) en el sistema bajo riego para condiciones de bosque seco espinoso- Jaén y Bagua” - Salazar Cubas, Nelly (2003)
The present investigation work was executed respectively in the counties of Utcubamba, Bagua and Jaén. Of the departments of Amazons and Cajamarca, having as main objective to determine the adaptability of 6 lines promising of rice in 3 towns of thorny dry forest for that which the design of blocks was used randomized completely with combinad variance analysis, having as materials of study 6 promissory lines and 5 commercial varieties distributed in 3 blocks, and 33 sub parcels for each town. The study material used in the investigation rehearsal Huarangopampa carne from the Experimental Station, likewise a commercial variety coming from the Rice Federation of Colombia (Fedearroz). In the conduction of the experiment, a halftechnological level was used. Carried out the statistical analysis you concluded that the varieties T9 (INIA Bijao 501) and T10 (1 Live) they registered the highest averages for the yield of the grain, while in what concerns to lines T3 (IR69595-9-KKL-4-4-BN-21-1-B) the only line that he/she obtained an acceptable average was.